2011
DOI: 10.1016/j.tube.2011.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oral lactoferrin on Mycobacterium tuberculosis induced immunopathology

Abstract: SUMMARY The ability of lactoferrin to provide protection and decrease immunopathology in infectious diseases was evaluated using an aggressive aerosol model of Mycobacterium tuberculosis (MTB) infection. C57BL/6 mice were challenged with MTB strain Erdman and treated with 0.5% bovine lactoferrin added to the drinking water starting at day 0 or day 7 post infection. Mice were sacrificed at three weeks post-challenge and evaluated for organ bacterial burden, lung histopathology, and ELISpot analysis of the lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 50 publications
4
32
1
Order By: Relevance
“…In this study, mice that received drinking water containing 0.5% bLf at Day 0 or 7 post-infection had lower Colony Forming Units (CFU) and lower inflammation in the lungs, with increased numbers of IFNγ producing T CD4 and CD8 cells and IL-17 producing lymphocytes when compared with animals vaccinated with BCG alone [114]. Noteworthy, bLf did not affect the in vitro replication of M. tuberculosis but instead enhanced the killing of bacteria by macrophages in a nitric oxide dependent way [114]. These studies using the models of pulmonary infection with M. tuberculosis suggest that Lf promotes certain up-regulation of pro-inflammatory response, while down-regulating overall tissue immunopathology.…”
Section: Lactoferrin As Anti-inflammatory In Infectious Diseasesmentioning
confidence: 99%
“…In this study, mice that received drinking water containing 0.5% bLf at Day 0 or 7 post-infection had lower Colony Forming Units (CFU) and lower inflammation in the lungs, with increased numbers of IFNγ producing T CD4 and CD8 cells and IL-17 producing lymphocytes when compared with animals vaccinated with BCG alone [114]. Noteworthy, bLf did not affect the in vitro replication of M. tuberculosis but instead enhanced the killing of bacteria by macrophages in a nitric oxide dependent way [114]. These studies using the models of pulmonary infection with M. tuberculosis suggest that Lf promotes certain up-regulation of pro-inflammatory response, while down-regulating overall tissue immunopathology.…”
Section: Lactoferrin As Anti-inflammatory In Infectious Diseasesmentioning
confidence: 99%
“…Finally, lactoferrin is a protein contained in secretions, including milk, that binds to iron and has antimicrobial properties. Mice infected with M. tuberculosis and fed lactoferrin had lower bacterial loads and less lung pathology than M. tuberculosis-infected mice not fed lactoferrin (119).…”
Section: Siderophores and Iron Sequestrationmentioning
confidence: 88%
“…The concept to use LF for treatment of sepsis is not unique, given the protein’s ability to limit bacterial growth, and to suppress microbial-induced inflammation in a variety of animal models (20, 2835). Our previous studies using bovine LF in the mouse model of MRSA challenge showed similar (modest) improvements in host survival concurrent with decreased serum cytokines (18).…”
Section: Discussionmentioning
confidence: 99%